A common deep source for upper-mantle upwellings below the Ibero-western Maghreb region from teleseismic P-wave travel-time tomography - Civiero, Chiara (2018)
Upper-mantle upwellings are often invoked as the cause of Cenozoic volcanism in the Ibero-western Maghreb region. However, their nature, geometry and origin are unclear. This study takes advantage of dense seismic networks, which cover an area extending from the Pyrenees in the north to the Canaries in the south, to provide a new high-resolution P-wave velocity model of the upper-mantle and topmost lower-mantle structure. Our images show three subvertical upper-mantle upwellings below the Canaries, the Atlas Ranges and the Gibraltar Arc, which appear to be rooted beneath the upper-mantle transition zone (MTZ). Two other mantle upwellings beneath the eastern Rif and eastern Betics surround the Gibraltar subduction zone. We propose a new geodynamic model in which narrow upper-mantle upwellings below the Canaries, the Atlas Ranges and the Gibraltar Arc rise from a laterally-propagating layer of material below the MTZ, which in turn is fed by a common deep source below the Canaries. In the Gibraltar region, the deeply rooted upwelling interacts with the Gibraltar slab. Quasi-toroidal flow driven by slab rollback induces the hot mantle material to flow around the slab, creating the two low-velocity anomalies below the eastern Betics and eastern Rif. Our results suggest that the Central Atlantic plume is a likely source of hot mantle material for upper-mantle upwellings in the Ibero-western Maghreb region.